Sub-central Tax Autonomy 2011 Update - Blöchliger, Hansjörg (OECD Working Papers on Fiscal Federalism, 2015)
This paper provides an update of the indicators that measure the tax autonomy of sub-central governments in OECD countries. Over the last decade, tax autonomy at the state level increased, while it hardly changed at the local level. The OECD now has tax autonomy indicators for the years 1995, 2002, 2005, 2008 and 2011